2022
DOI: 10.1007/s10758-022-09620-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Support Units in Digital Transformation: How Institutional Entrepreneurs Build Capacity for Online Learning in Higher Education

Abstract: This study used New Institutional Theory to explore how entrepreneurial activities in support units contribute to digital transformation in higher education in Norway. We describe how entrepreneurs initiated and operationalized support for Massive Open Online Courses (MOOCs), micro-credentials and fully online courses in pockets of innovation within existing institutional arrangements. An ambition was to understand why capacity building for digital transformation in a country described by the Organization for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, the implementation of organizations' lifelong learning varies across countries, or even across regions in the same country or organizations in the same region (Guitert et al, 2021). Prior research has also suggested that is essential to explore how to support individual learning and development in the context of emerging economies (Langseth et al, 2023;Zajac et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…However, the implementation of organizations' lifelong learning varies across countries, or even across regions in the same country or organizations in the same region (Guitert et al, 2021). Prior research has also suggested that is essential to explore how to support individual learning and development in the context of emerging economies (Langseth et al, 2023;Zajac et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of digital learning clusters discusses various perspectives on digital devices that support the learning process. According to this analysis, initiatives to offer online learning entail open digital platforms, pedagogy for online course creation, and support for higher education (Langseth et al 2022). Mobile business simulation games can be used to teach digital lessons in entrepreneurship education, which can improve students' entrepreneurial attitudes, self-efficacy, and inclinations (Chen et al, 2022;Shabbir, 2021).…”
Section: The Primary Research Abstract and Author Collaboration Netwo...mentioning
confidence: 99%
“…akin to Steffens' argument of an additional society and value-driven goal of lifelong learning). In their research of MOOCs in Norway, Langseth et al (2021) argued that governmental bodies and institutional stakeholders should give more attention to MOOC initiatives to develop sustainability in flexible and lifelong learning in higher education institutions. MOOCs have been found to play a role in the context of sustainability especially for their possibility to enable the sharing of ideas, confirm principles and build networks and contacts.…”
Section: Understanding the Connection Between Lifelong Learning And M...mentioning
confidence: 99%